Bionic Robots: Definition and Their Relevance in Biochemistry and Immunology - Sabbar, Ahmed Gh; Dohi, Fatima A (Bio-Robotics, 2025)
Bionic robots constitute a fusion of biological ideas with advanced robotics, permitting machines to mimic and combine with dwelling systems. Their relevance in biochemistry and immunology extends past mechanical engineering, influencing biomedical programs such as prosthetics, immune-modulating devices, and biohybrid structures. This record explores the definition of bionic robots, their biochemical interactions, and their immunological implications, highlighting their transformative capacity in medication and biotechnology. Bionic robots, stimulated by using biological structures, combine biomimetic standards to enhance adaptability, sensory belief, and functional efficiency. This overview explores the biochemical and immunological implications of bionic robotics, specializing in biohybrid designs, immune responses to synthetic materials, and capability packages in remedy and biotechnology.